Combination of Multiplex PCR and PCR-Denaturing Gradient Gel Electrophoresis for Monitoring Common Sourdough-Associated Lactobacillus Species - Settanni, Luca (American Society for Microbiology, 2006)
A combination of denaturing gradient gel electrophoresis (DGGE) and a previously described multiplex PCR approach was employed to detect sourdough lactobacilli. Primers specific for certain groups of Lactobacillus spp. were used to amplify fragments, which were analyzed by DGGE. DGGE profiles obtained from Lactobacillus type strains acted as standards to analyze lactobacilli from four regional Abruzzo (central Italy) sourdoughs.